PENGARUH WORD OF MOUTH DAN DESTINATION IMAGE TERHADAP VISIT INTENTION DAN VISIT DECISION (Studi Kasus Pada Wisata Alam Bukit Kelam, Kabupaten Sintang) - Setia, Setia Poliawati B1021141081 (Jurnal Manajemen Update, 2017)
Destination Image on Visit Intention and Visit Decision (case study at Taman Wisata Alam Bukit Kelam, Sintang District). This research type is explanatory research with quantitative approach. The population in this study is the people of West Kalimantan and outside West Kalimantan who had visited the Taman Wisata Alam Bukit Kelam, Sintang District. The number of samples of 100 respondents selected by way of purposive sampling, then processing the data using path analysis. The results of analysis for the first model show that the variables of word of mouth and destination image had a significant positive effect on visit intention. Result of research for second model shows that word of mouth and visit intention have positive effect to visit decision, while variable destination image has no significant positive effect to visit decision.Â